Pengaruh Harga, Kualitas Produk, Label Halal Terhadap Pembelian kembali Produk Kosmetik X Melalui Kepuasan Konsumen Sebagai Pemediasi - Faiq Yash Bahy Nuryanto; Muhammad Sholahuddin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the effect of price, product quality, and halal label on repurchase of Wardah cosmetic products, with consumer satisfaction as a mediating variable. A quantitative approach was used with a survey method through an online questionnaire distributed to 147 respondents, namely followers of the Instagram account @wardahbeauty who were over 18 years old and had purchased Wardah products more than once. Data analysis was carried out using SEM-PLS which included testing the outer model and inner model. The results showed that price and product quality had a significant effect on consumer satisfaction and repurchase, while the halal label did not have a significant effect on either. Consumer satisfaction was shown to mediate the relationship between price and repurchase, as well as between product quality and repurchase. The novelty of this study lies in the inclusion of the halal label as a variable in the context of the halal cosmetic market, which has not been studied in depth. This study also fills the gap from previous studies that have not explored the role of the halal label and consumer satisfaction as mediators in repurchase decisions. This study contributes to enriching the halal cosmetic marketing literature by showing that the halal label is not always the main determinant in the formation of consumer satisfaction and repurchase intentions.